Preservation of Cell Structure, Metabolism, and Biotransformation Activity of Liver‐On‐Chip Organ Models by Hypothermic Storage. Issue 2 (27th September 2017) - Gröger, Marko; Dinger, Julia; Kiehntopf, Michael; Peters, Frank T.; Rauen, Ursula; Mosig, Alexander S.
Abstract: The liver is a central organ in the metabolization of nutrition, endogenous and exogenous substances, and xenobiotic drugs. The emerging organ‐on‐chip technology has paved the way to model essential liver functions as well as certain aspects of liver disease in vitro in liver‐on‐chip models. However, a broader use of this technology in biomedical research is limited by a lack of protocols that enable the short‐term preservation of preassembled liver‐on‐chip models for stocking or delivery to researchers outside the bioengineering community. For the first time, this study tested the ability of hypothermic storage of liver‐on‐chip models to preserve cell viability, tissue morphology, metabolism and biotransformation activity. In a systematic study with different preservation solutions, liver‐on‐chip function can be preserved for up to 2 d using a derivative of the tissue preservation solution TiProtec, containing high chloride ion concentrations and the iron chelators LK614 and deferoxamine, supplemented with polyethylene glycol (PEG). Hypothermic storage in this solution represents a promising method to preserve liver‐on‐chip function for at least 2 d and allows an easier access to liver‐on‐chip technology and its versatile and flexible use in biomedical research. Abstract : Liver‐on‐chip has paved the way to model individual organ functions and disease aspects in vitro. However, due to the lack of reliable protocols for short‐term preservation (i.e., for stocking or shipment) its broader use is still limited. This study describes the use of specifically designed storage solutions that fully preserve liver‐on‐chip function for at least 2 d during hypothermic storage.